Guar gum: A novel binder for ceramic extrusion. Issue 18 (15th December 2017) - Elbadawi, M.; Mosalagae, M.; Reaney, I.M.; Meredith, J.
Abstract: Ceramic honeycomb extrusion is a technique capable of attaining high strength, porous ceramics. However, challenges prevent the realisation of its potential. These include the design of an intricate honeycomb die and the formulation of an extrudable paste. The present study addresses the latter by using guar gum (GG) as a binder. GG was rationally selected because hydrogels thereof exhibit strong shear-thinning and high stiffness properties, which are required for extrusion. Rheological analyses demonstrated ceramic pastes with similar qualities were achieved, with hydroxyapatite (HA) used as the model ceramic. The shear stiffness modulus of HA pastes was determined as 8.4 MPa with a yield stress of 1.1 kPa. Moreover, this was achieved with GG as the sole additive, which further facilitates the overall fabrication process. The binder extraction notably occurred at relatively low temperatures when other high molecular weight polymers demand temperatures above 1000 °C; therefore the latter precludes the use of ceramics with low sintering onset. The process culminated in a porous HA scaffold with similar porosity to that of a commercial HA graft, but with higher compressive strength. Lastly, the study notes that the biological and water-soluble properties of GG can broaden its application into other ceramic fabrication processes.